KRITIK WACANA TAFSIR GENDER : RELASI GENDER DALAM AL-QUR’AN - Faisal Abdullah (AL-BAYAN INSTITUTE, 2025)
This article focuses on the discourse of interpretation of gender verses from the perspective of classical and contemporary interpreters, emphasizing the ever-evolving scientific discourse compared to the immutable message of the Qur'an. This research is a library research, namely examining library materials or literature related to the research problem by selecting, reading, reviewing and examining books or other written sources that are relevant to the research title contained in the library sources. The approach used is a qualitative analysis approach based on the Islamic Worldview paradigm offered by Syed Muhammad Naquib Al-Attas. This study is intended to produce descriptive data in the form of written data after conducting a thought analysis (content analysis) of a text. The conclusion of this study, the differences in the interpretation of the Qur'an are due to different approaches in the interpretation of the Qur'an, textual approaches (bil ma'tsur) to interdisciplinary approaches (bil ra'yi), resulting in the emergence of different interpretation products. Our findings in this study lie at the meeting point of the two interpretation products from a socio-historical perspective, where the Qur'an is very dynamic in responding to the needs of the people in their respective eras, so that it is very likely that an interpretation product will emerge that remains up to date in the future.